Divergence of State Concepts in Online Media: A Comparative Study of Dar al-Islam and Dar al-Salam Perspective by Religious Organization - Ali Mursyid Azisi; Kunawi Basyir; Muhammad Taqiyuddin Iqbal Faiz; Fakky Fahrisal Nur (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
This research examines the contestation of Muslim religious patterns in Indonesia, especially on social media. Contestation of the meaning of the state or state system from an Islamic perspective is echoed by extreme and moderate Islam. Extreme-conservative religious patterns tend to interpret democracy as a product of infidels and a political game of chameleons, even thagut. A moderate Islamic camp supports the democratic system on the grounds that it is for the benefit of citizens who are not only Muslims. The data objects studied in this article were taken from @almanhaj. or.id, @safaridakwah, www.almanhaj.or.id and @ulama.nusantara, @nahdlatululama, www.nu.or.id. The research method used in this study was qualitative, using literature studies and processing data objects taken from social media channels and websites. The identity of this article is also a media/netnography study, whose processing process begins with collecting data (virtual observation), which is then analyzed and processed using Teun A. Van Dijk's discourse analysis theory, which consists of text, social cognition, and social context. Finally, this article concludes that the concept of the true and ideal state from extremes is the caliphate system and the enforcement of Islamic law in the state against anyone, regardless of any religious background known as dar al-islam. In contrast to moderates, who interpret democracy as a good state concept to be applied in multi-religious Indonesia known as Dar al-Salam. This view of moderates cannot be separated from Prophet's command, namely, in the state to emphasize the benefits for all groups. The theoretical implication in this study is that the state system built and narrated in the digital space by Muslims has two poles, namely the Islamic state "dar al-islam" and the prosperous, peaceful state "Dar al-salam.” The discovery of these two major concepts is an academic contribution resulting from the study of the meaning of the state in the digital space by religious organizations in Indonesia. Thus, this study provides benefits for future researchers in developing Islamic studies and statehoods from an Islamic perspective.